TEACHING ENGLISH VOCABULARY USING PICTURE IN EIGHTH GRADE OF JUNIOR HIGH SCHOOL - Restu Anggi Winita; Fairuz Sopiya Rasyida (PROJECT (Professional Journal of English Education), 2018)
This research focused with teaching English vocabulary using picture in eight grade of junior high school. This research explores the implementation of English vocabulary and to find out the score improvement in using picture in learning process. The objective of this research is to find out the effectiveness of picture in improving students’ vocabulary. Data collection technique focus on pretest and posttest. Picture is a good media to make everything like real and can visualize to the lesson environtment.  The means score of pretest was 42.33 and the posttest get improve to 76.50. It could also be concuded that teaching English vocabulary using picture was effective media to improve students’ vocabulary.